Sosialisasi dan Bimbingan Penyusunan Laporan Keuangan sesuai dengan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) kepada Pengelola UMKM - Silmi Silmi; Laura Amelia Triani; Berri Brilliant Albar; Indah Permata Suryani (Warta Pengabdian Andalas, 2023)
Financial reports are financial information about a business entity that must be prepared by business entity managers, including managers of Micro, Small and Medium Enterprises (MSMEs). The Indonesian Accountants Association sets two standards that MSMEs can use as guidelines in preparing their financial reports. The two standards are the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) and the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). MSME managers are free to choose both standards with the condition that they must be consistent in each report. Therefore, a webinar activity was needed for MSME managers regarding SAK ETAP and SAK EMKM. This webinar was attended by 52 participants from various MSMEs in Indonesia. The webinar implementation method consisted of 3 stages; (1) introduction of SAK EMKM, (2) applied of SAK EMKM, and (3) discussions. This webinar provided knowledge and information to MSMEs managers to be developed and applied in preparing financial reports for their MSMEs.